2010
DOI: 10.1016/j.drugalcdep.2009.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine use parameters do not predict neuropsychological impairment in currently abstinent dependent adults

Abstract: Methamphetamine (meth) abuse is increasingly of public health concern and has been associated with neurocognitive dysfunction. Some previous studies have been hampered by background differences between meth users and comparison subjects, as well as unknown HIV and hepatitis C (HCV) status, which can also affect brain functioning. We compared the neurocognitive functioning of 54 meth dependent (METH+) study participants who had been abstinent for an average of 129 days, to that of 46 demographically comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 76 publications
(73 reference statements)
7
49
2
Order By: Relevance
“…Rather, it is possible that binge episodes differentially contribute to cognitive decline, perhaps particularly in individuals who have not yet developed considerable tolerance to the drug (Segal et al, 2003). Cherner et al (2010b) did not find a relationship between cognitive function and binge patterns in MAdependent humans, but to our knowledge, this is the only study to have examined this issue.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Rather, it is possible that binge episodes differentially contribute to cognitive decline, perhaps particularly in individuals who have not yet developed considerable tolerance to the drug (Segal et al, 2003). Cherner et al (2010b) did not find a relationship between cognitive function and binge patterns in MAdependent humans, but to our knowledge, this is the only study to have examined this issue.…”
Section: Discussionmentioning
confidence: 64%
“…To our knowledge, only one study has examined the relationship between parameters of MA use and cognitive function in a primary analysis. In that study (Cherner et al, 2010b), parameters of MA use for MA-dependent participants who were cognitively impaired (at least mild impairment in two or more cognitive domains based on demographically adjusted norms) were compared with those of MA-dependent participants who were not impaired on a comprehensive cognitive battery. The results revealed that the cognitively impaired and non-impaired groups did not differ on any index of MA use, including years of use, lifetime grams consumed, average grams used per year, length of abstinence, method of administration, bingeing pattern, or age of initiation.…”
Section: Cognitive Deficits In Ma-abusing Individuals Will Be Dose-rementioning
confidence: 99%
See 1 more Smart Citation
“…Detailed interviews were conducted with each participant to ascertain approximations of cumulative amount of past year cannabis, alcohol and tobacco use. This approach employed modified timeline follow-back procedures, similar to methods employed in other studies (Cherner et al, 2010; Gonzalez et al, 2012; Rippeth et al, 2004; Schuster et al, 2012), and involved gathering retrospective estimates of amount of daily cannabis (reported in or converted to grams), alcohol (reported in or converted to standard drinks) and tobacco (reported in or converted to cigarettes) use over the year prior to the study visit. Amount of use per substance was summed to arrive at a cumulative estimate of amount of past year consumption.…”
Section: Methodsmentioning
confidence: 99%
“…Methamphetamine (METH) is an addictive psychostimulant that dramatically affects the central nervous system (CNS) [7]. Recent findings have shown that chronic METH use alters synaptic plasticity in the brain, which may contribute to its adverse effects [35], include dependence, withdrawal syndrome and drug craving [9,17,34].…”
Section: Introductionmentioning
confidence: 99%